Beowulf Cluster Systems in Academic Environment at Kasetsart University - Uthayopas, Putchong; Sanguanpong, Surasak; Poovarawan, Yuen (Agriculture and Natural Resources, 2001)
In the past, having a supercomputer seems to be impossible for a university in Thailand due to the high cost of the system. There used to be only one or two supercomputers in the whole country. This situation severely limits the application of computational science for the industry and the growth of researches in this area. Recent adoption of Beowulf clustering technology has changed the situation dramatically, especially at Kasetsart University. This paper presents the use of Beowulf Cluster System to support academic activities at Kasetsart University, Bangkok, Thailand. The background, history, and development of Beowulf related activities are discussed. Currently, the cluster system has been used to support computer engineering courses and many general-computing services at the university level. In addition, many research projects that never been existed before, have started with the building of this new cluster system. From our experiences, Beowulf cluster systems are very useful tool that open many new opportunities for research and teaching in our organization.